ANSWER:
![\begin{gathered} x+2z=1 \\ y-5z=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xqf6x21e1mjfe5m412qn37tyuj7jp0x8dv.png)
The solution is:
![\begin{gathered} x=1-2z \\ y=3+5z \\ z=z \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2kin77u1nvdac6jcdpcmjeqsgep5g047k6.png)
Explanation:
We must convert the matrix into a system of linear equations.
Each vertical represents the letters x, y and z, the first the x, the second y and the third the z. The fourth value is the value of the independent term that would be equal to the other expression, just like this:
![\begin{gathered} 1x+0y+2z=1 \\ 0x+1y-5z=3 \\ 0x+0y+0z=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zbna7e4uqenbf2i82fovgk7my1gch4cdtn.png)
We operate and the system will finally be like this
![\begin{gathered} x+2z=1 \\ y-5z=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xqf6x21e1mjfe5m412qn37tyuj7jp0x8dv.png)
let's solve the system and we have:
![\begin{gathered} x=1-2z \\ y=3+5z \\ z=z \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2kin77u1nvdac6jcdpcmjeqsgep5g047k6.png)